MULTIDIMENSIONAL RELIABILITY OF INSTRUMENT STUDENTS’ SATISFACTION USING CONFIRMATORY FACTOR ANALYSIS - Margono, Gaguk (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2014)
The purpose of this paper is to compare unidimensional reliability and multidimensional reliability of instrument students’ satisfaction as an internal costumer. Multidimensional reliability measurement is rarely used in the field of research. Multidimensional reliability is estimated by using Confirmatory Factor Analysis (CFA) on the Structural Equation Model (SEM). Measurements and calculations are described in this article using instrument students’ satisfaction as an internal costumer. Survey method used in this study and sampling used simple random sampling. This instrument has been tried out to 173 students. The result is concluded that the measuringinstrument of students’ satisfaction as an internal costumer by using multidimensional reliability coefficient has higher accuracy when compared with a unidimensional reliability coefficient. Expected in advanced research used another formula multidimensional reliability, including when using SEM. Keywords: multidimensional reliability, instrumentof students’ satisfaction as an internal costumer, confirmatory factor analysis.